ANALISA MODEL PEMBELAJARAN STUDENT CENTRED LEARNING - Indayani, Endang; Hartini, Sri (unprimdn.ac.id, 2024)
Student-Centered Learning (SCL) is a learning model that places students at the center of the learning process, encouraging them to be more active, independent, and responsible in understanding the material. In the Merdeka Curriculum, this model provides flexibility for educators to design more relevant learning experiences. Several methods within SCL include Student Team Achievement Division (STAD), Small Group Discussion, Discovery Learning, Cooperative Learning, and Project-Based Learning (PjBL). The STAD method is widely applied as it emphasizes teamwork in understanding the material while maintaining individual evaluation. This learning model has been proven to enhance students’ motivation, critical thinking skills, and social interaction. However, implementing SCL also comes with challenges, such as requiring more time and demanding teachers to take on a more active role as facilitators. With proper implementation, SCL can help students achieve better comprehension and develop essential skills for both academic and professional success.